PENINGKATAN KEMAMPUAN SISWA MENULIS BAHASA INGGRIS NARRATIVE TEXT MELALUI MEDIA GAMBAR BERSERI - Nurhayati Nurhayati (Jurnal Pendidikan, 2018)
The aim of this study is to improve students’ ability in writing narrative text in English by using picture series media. The object of this study is the Eighth grade students of one-roof Junior High School Teratak Baru Kuantan Hilir district. This study used the quantitative classroom action research which was carried out in 2 cycles, in this study the data collection technique used observation and tests (pre-test and post-test). The result of this study showed that there is an increasing in learning by students of eighth grade, consequently it can be concluded that by utilizing picture series media can improve students’ ability in writing English narrative text. It can be seen from the result of the average post-test in cycle 2 of 80 increased to85. The result of the observation showed that the teacher’s activities in teaching increased in both early condition in the cycle I and cycle II.